2012
DOI: 10.1167/iovs.12-10198
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Aptamer Targeting TGF-β Receptor II Inhibits Transdifferentiation of Human Tenon's Fibroblasts into Myofibroblast

Abstract: Our study revealed that a novel aptamer binding TβRII inhibited TGF-β2-induced myofibroblast transdifferentiation in HTFs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…Contraction of a collagen gel mediated by human Tenon's capsule fibroblasts (HTFs) has thus been studied as a model of subconjunctival wound healing 3. The cytokine transforming growth factor β (TGF-β) is a key mediator of wound healing and tissue repair.…”
Section: Introductionmentioning
confidence: 99%
“…Contraction of a collagen gel mediated by human Tenon's capsule fibroblasts (HTFs) has thus been studied as a model of subconjunctival wound healing 3. The cytokine transforming growth factor β (TGF-β) is a key mediator of wound healing and tissue repair.…”
Section: Introductionmentioning
confidence: 99%
“…Neither of the two peptides could bind to e.g., BMPR–IA (Alk3), ActRII (which also binds BMPs) and the co-receptors β-glycan and endoglin [78]. More recently, aptamers were raised (using SELEX) against the extracellular domain of TβRII and used in vitro to investigate the TGFβ-induced myofibroblast transdifferentiation of human Tenon’s fibroblasts [79]. In particular, the aptamer S58 was found to antagonize the effects of TGFβ2 on differentiation, as the aptamer interferes with activation and nuclear translocation of Smad2.…”
Section: Aptamers and Their Use In Targeting Of Signal Transductiomentioning
confidence: 99%
“…In particular, the aptamer S58 was found to antagonize the effects of TGFβ2 on differentiation, as the aptamer interferes with activation and nuclear translocation of Smad2. Transdifferentiated myofibroblasts show increased contractile activity associated with de novo expression of α-Smooth Muslce Actin (α-SMA), which is downregulated by S58 [79]. …”
Section: Aptamers and Their Use In Targeting Of Signal Transductiomentioning
confidence: 99%
“…The TGF-β family is the main stimulator leading to conjunctival scarring post trabeculectomy, and various cells, such as fibroblasts and macrophages, can secrete them [15]. It was previously reported that TGF-β2 could increase α-smooth muscle actin (α-SMA) expression and the transdifferentiation of fibroblasts in conjunctiva to myofibroblasts [16]. In another previous study, the authors’ findings revealed that bleb failure post trabeculectomy primarily occurred due to the excessive accumulation of collagen in the subconjunctival space, and that high activity of TGF-β was associated with scarring [17].…”
Section: Introductionmentioning
confidence: 99%